2004
DOI: 10.1037/0022-006x.72.3.479
|View full text |Cite
|
Sign up to set email alerts
|

The Hartford Study of Supported Employment for Persons With Severe Mental Illness.

Abstract: The authors compared 3 approaches to vocational rehabilitation for severe mental illness (SMI): the individual placement and support (IPS) model of supported employment, a psychosocial rehabilitation (PSR) program, and standard services. Two hundred four unemployed clients (46% African American, 30% Latino) with SMI were randomly assigned to IPS, PSR, or standard services and followed for 2 years. Clients in IPS had significantly better employment outcomes than clients in PSR and standard services, including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
218
5
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(239 citation statements)
references
References 66 publications
(82 reference statements)
12
218
5
4
Order By: Relevance
“…In cases of job tenure and wages earned, when mean and standard deviations were unavailable, SMDs were calculated from t-test values, F-tests or Z-tests. For studies that compared three vocational approaches, using one intervention as a control condition [26,27], we followed the recommendations of the Cochrane Collaboration and divided the control group into two equal groups, so the total number of participants in both groups made up the size of the original sample. Heterogeneity was examined using the Q test [28] Table 1).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of job tenure and wages earned, when mean and standard deviations were unavailable, SMDs were calculated from t-test values, F-tests or Z-tests. For studies that compared three vocational approaches, using one intervention as a control condition [26,27], we followed the recommendations of the Cochrane Collaboration and divided the control group into two equal groups, so the total number of participants in both groups made up the size of the original sample. Heterogeneity was examined using the Q test [28] Table 1).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Trials targeting competitive job tenure did not report a significant difference between treatment and control in terms of hours worked (SMD = 0.88, 95% CI: -0.25-2.01, p = 0.12) or weeks used for addressing cognitive impairments for people with schizophrenia; cognitive-behavioral interventions were targeted to address dysfunctional beliefs and to assess their influence on experiences and work. Two studies compared three approaches to vocational rehabilitation [26,27]. The study by Mueser et al [26] used individual placement and support, psychosocial rehabilitation and standard services including supported employment; the study by Tsang et al [27] used integrated supported employment defined as an individual placement and support augmented with social skills training, individual placement and support alone, and traditional vocational rehabilitation, which included pre-vocational training.…”
Section: Job Tenurementioning
confidence: 99%
See 1 more Smart Citation
“…Those who obtain CE via IPS have been shown to have improved self-esteem, quality of life, social inclusion, and psychiatric symptoms [20,[31][32][33], and improvements have been shown to be maintained during follow-up, for as many as 12 yr [7,34]. Although IPS has been associated with improvements in some nonvocational outcomes in observational outcome studies, these improvements have not been greater than those demonstrated by other rehabilitation programs when evaluated in randomized trials [33,[35][36][37][38]. Several other studies that favored IPS with regard to vocational outcomes failed to find greater improvement in non-vocational outcomes [27,37].…”
Section: Supported Employmentmentioning
confidence: 99%
“…Respecto de datos específicos relativos a la obtención de empleo competitivo se observó una diferencia notoria entre el IPS y los otros programas (27% vs. 7%). Por su parte, el equipo de Mueser et al 53 comparó tres métodos de inserción profesional en población psiquiátrica, entre ellos el modelo IPS. Los usuarios de IPS tuvieron una mayor empleabilidad competitiva (73.9%) que los usuarios de los otros dos métodos (18.2% y 27.5%).…”
Section: • Puestos De Trabajo En Empresas Ordinarias En Condiciones Deunclassified